2016
DOI: 10.1515/hukin-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Responses and Body Composition Changes Following Resistance Training Under Normobaric Hypoxia

Abstract: The aim of the present study was to evaluate the effects of a 6 week resistance training protocol under hypoxic conditions (FiO2 = 12.9%, 4000 m) on muscle hypertrophy. The project included 12 resistance trained male subjects, randomly divided into two experimental groups. Group 1 (n = 6; age 21 ± 2.4 years; body height [BH] 178.8 ± 7.3 cm; body mass [BM] 80.6 ± 12.3 kg) and group 2 (n = 6; age 22 ± 1.5 years; BH 177.8 ± 3.7cm; BM 81.1 ± 7.5 kg). Each group performed resistance exercises alternately under norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 22 publications
(25 reference statements)
2
44
0
Order By: Relevance
“…Even though the exposure to hypoxia as well as exercise under hypoxia is positively associated with the loss of body fat (Netzer et al, 2008(Netzer et al, , 2015, no changes of the FM were achieved in the current study. This result is in line with previous RTH studies that also did not find any effects on body fat (Ho et al, 2014b;Chycki et al, 2016;Martínez-Guardado et al, 2019). There are two RTH studies by Kon et al (2014) and Yan et al (2016) showing a significantly reduced FM between −1 and −2%, but without significant differences to the group who performed resistance training under normoxia.…”
Section: Effects Of Rth On Body Compositionsupporting
confidence: 92%
See 2 more Smart Citations
“…Even though the exposure to hypoxia as well as exercise under hypoxia is positively associated with the loss of body fat (Netzer et al, 2008(Netzer et al, , 2015, no changes of the FM were achieved in the current study. This result is in line with previous RTH studies that also did not find any effects on body fat (Ho et al, 2014b;Chycki et al, 2016;Martínez-Guardado et al, 2019). There are two RTH studies by Kon et al (2014) and Yan et al (2016) showing a significantly reduced FM between −1 and −2%, but without significant differences to the group who performed resistance training under normoxia.…”
Section: Effects Of Rth On Body Compositionsupporting
confidence: 92%
“…Body composition, and in particular the FFM or lean body mass, was analyzed in previous RTH studies to indirectly research the effect of this type of intervention on muscle mass/muscular hypertrophy (Ho et al, 2014b;Kon et al, 2014;Chycki et al, 2016;Yan et al, 2016;Martínez-Guardado et al, 2019). We did not observe any changes regarding the FFM which is in line with the insights from the meta-analysis by Ramos-Campo et al (2018b) stating that there is only a small to non-significant effect regarding the increase of the muscle size with RTH compared to RT under normoxia.…”
Section: Effects Of Rth On Body Compositionsupporting
confidence: 82%
See 1 more Smart Citation
“…This data indicates that the chronic exposure to high altitude through a reduction in overall exercise activity may have a harmful effect on muscle tissue as a result of decreased synthesis of muscle proteins [ 21 , 56 ], leading to atrophic changes in skeletal muscles. On the other hand, our latest reports [ 57 ] and the studies of other researchers [ 58 , 59 ] suggest that acute short-term exposure (one to two hours), especially if combined with resistance exercise has a contrary effect on muscle tissue by stimulation of muscle protein synthesis.…”
Section: Resultsmentioning
confidence: 98%
“…7 At a molecular level, resistance training promotes insulin-like growth factor-1(IGF1), interleukin-6 (IL-6)/signal transducer and activator of transcription 3 (STAT3), and Hippo cellular pathways, which are known to foster myogenesis through the direct regulation of MRF. 15,16 Based on these observations, several studies have demonstrated that intermittent hypoxia potentiates muscle hypertrophy and/or strength induced by resistance training [17][18][19][20] (even if other authors showed equivocal results 21 ); however, the mechanisms involved in this process are largely unknown. 15,16 Based on these observations, several studies have demonstrated that intermittent hypoxia potentiates muscle hypertrophy and/or strength induced by resistance training [17][18][19][20] (even if other authors showed equivocal results 21 ); however, the mechanisms involved in this process are largely unknown.…”
Section: Introductionmentioning
confidence: 99%